Mental Health Assessment of the Population: Study Protocol of the MAP Research Program in Ukraine (MAP-U) and in Zurich (MAP-Z) - Viktoriia Yasenok; Eileen Neumann; Alessia Raineri; Julia Kopp; Seraina Rüegger; Tala Ballouz; Marco Kaufmann; Andrii Loboda; Vladyslav Smiianov; Andreas M. Baumer; Andreas M. Baumer; Erich Seifritz; et al. (International Journal of Public Health)
ObjectivesTo conduct mental health surveillance in adults in Ukraine and Ukrainian refugees (Canton of Zurich, Switzerland) as an actionable scientific foundation for public mental health and mental healthcare.MethodsMental Health Assessment of the Population (MAP) is a research program including prospective, population-based, digital cohort studies focused on mental health monitoring. The study aims to include 17,400 people from the general population of Ukraine, 1,220 Ukrainians with refugee status S residing in the canton of Zurich, and 1,740 people from the Zurich general population. The primary endpoints are prevalence and incidence of symptoms of: posttraumatic stress disorder (measured by PCL-5), depression (PHQ-9), anxiety (GAD-7), and alcohol use disorder (AUDIT). Secondary endpoints include participants’ health-related quality of life (EQ-5D-5L and EQ-VAS), experiences of somatic distress syndrome (PHQ-15), social isolation, social integration, and mental wellbeing (SWEMWBS).ResultsBaseline assessment starts in March 2024 with follow-ups occurring every 3 months for at least 2 years.ConclusionMAP will generate reliable, comparable, and high-quality epidemiological data to inform public mental health and healthcare policies in the Ukrainian population.ISRCTN Registryhttps://www.isrctn.com/ISRCTN17240415.